Hope, atonement, and human rights behind bars: a critical re-examination of the “right to hope” - Marcar, GP (2023)

(untitled)
The “right to hope” (RtH) was first invoked by Judge Power-Forde in Vinter and Others v. UK (2013), in the context of the European Court of Human Rights’ ruling that “irreducible” life sentences contravene Article 3 ECHR’s prohibition on “inhuman or degrading treatment or punishment.” This dissertation re-examines the RtH’s normative and legal grounding, as well as some of the critiques raised against it.